1997
DOI: 10.1265/jjh.52.470
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between Lifestyles and Maximal Oxygen Uptake in Healthy Adults.

Abstract: In this study, to determine the influence of different lifestyles on maximal oxygen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that Asian males might have less smoking-related annual excess FEV1 declines, estimated 3 mL per pack years, as compared with other racial males [13,14]. In a Japanese male cohort, smoking was not associated with maximal oxygen uptake during treadmill exercise as well [15]. It is reasonable that the declines in lung function could lead to poor exercise performance.…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies have reported that Asian males might have less smoking-related annual excess FEV1 declines, estimated 3 mL per pack years, as compared with other racial males [13,14]. In a Japanese male cohort, smoking was not associated with maximal oxygen uptake during treadmill exercise as well [15]. It is reasonable that the declines in lung function could lead to poor exercise performance.…”
Section: Introductionmentioning
confidence: 78%
“…Leisure-time physical activity such as exercise is well known to be associated with maximal oxygen uptake (Kawabata et al 1997;Kelley and Kelley 2006), and it was reported that the physical activity questionnaire had an acceptable validity for estimating maximal oxygen uptake (Aadahl et al 2007). In multiple regression analysis, leisure-time physical activity rating was a statistically significant variable and had a positive relationship with maximal oxygen uptake (β = 0.701).…”
Section: Discussionmentioning
confidence: 96%
“…The factors associated with maximal oxygen uptake included genetics, age, gender, physical activity, body fat, smoking and medical conditions such as metabolic syndrome and diabetes (O'Tool 1989;Watanabe et al 1994;Chilibeck et al 1996;Kawabata et al 1997;Lim et al 1997;Hashizume et al 2000;Park et al 2001;Zhang et al 2004;An et al 2005;Kang et al 2005). Considering ethnical difference on maximal oxygen uptake, it is necessary to develop a non-exercise regression model for Korean adults (John et al 2011).…”
mentioning
confidence: 99%
“…The age of the present subjects were 38.7 9.9 yr for male, 38.0 8.9 yr for female; SBP were 117. 2 15.0 mmHg for male, 107.4 15.0 mmHg for female, and BMI were 23.1 3.0 for male, 21.6 3.2 for female.…”
Section: Validity Of Objectsmentioning
confidence: 88%